Practical investigation of the performance of robust logistic regression to predict the genetic risk of hypertension - Kesselmeier, Miriam; Legrand, Carine; Peil, Barbara; Kabisch, Maria; Fischer, Christine; Hamann, Ute; Lorenzo Bermejo, Justo (BMC proceedings, 2014)
Logistic regression is usually applied to investigate the association between inherited genetic variants and a binary disease phenotype. A limitation of standard methods used to estimate the parameters of logistic regression models is their strong dependence on a few observations deviating from the majority of the data.
Gesehen am 14.10.2020